If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -1(5x + -12) = 1 + 6x Reorder the terms: 12x + -1(-12 + 5x) = 1 + 6x 12x + (-12 * -1 + 5x * -1) = 1 + 6x 12x + (12 + -5x) = 1 + 6x Reorder the terms: 12 + 12x + -5x = 1 + 6x Combine like terms: 12x + -5x = 7x 12 + 7x = 1 + 6x Solving 12 + 7x = 1 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 12 + 7x + -6x = 1 + 6x + -6x Combine like terms: 7x + -6x = 1x 12 + 1x = 1 + 6x + -6x Combine like terms: 6x + -6x = 0 12 + 1x = 1 + 0 12 + 1x = 1 Add '-12' to each side of the equation. 12 + -12 + 1x = 1 + -12 Combine like terms: 12 + -12 = 0 0 + 1x = 1 + -12 1x = 1 + -12 Combine like terms: 1 + -12 = -11 1x = -11 Divide each side by '1'. x = -11 Simplifying x = -11
| f(x)=2x^2-3x-1 | | 9+13j=13j+2 | | a(a^2-2ab+b^2)= | | 2(x+2)x=6 | | 0.5x-y=2 | | -4+10t=-2-10t+20t | | (X+93)=4x | | 17(9-x)-5=52 | | 0=-4u+4u | | 10g-3=10g-2 | | 7x-28=4 | | 7x-28=48 | | -(1-8x)=31+4x | | -5n+9-4=-5n+5 | | 14mn+18m= | | 9x-5=45 | | -7(2x-1)+5(3x-2)-7=4-9 | | 7+5k=5k+1 | | 2x-3=8x-3(1+2x) | | 3x+7=-2x+5 | | 0=-7s+7s | | 4x-35=3+10 | | 5x+bx=7 | | 3(1+5x)-1=-103 | | -8.6q+13.32=-18.4q+6.04+9.1q | | 5x+6x+7=5x-7 | | 4x-2=13x+16 | | 2(15r+10)=-80 | | 17f+8=18f-6 | | 7w-w=6w | | (14x)Y-7=(7x)Y+7 | | 10b-8=10b+7 |